GASTRO-FLOATING TABLETS OF REPAGLINIDE: PREPARATION AND IN VIVO EVALUATION - P, Poornima; K, Abbulu; K, Mukkanti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Current research concerns the expansion of repaglinide matrix floating tablets, which are designed to prolong the gastric residence time, increase the drug bioavailability, and diminish the side effects. Methods: Different formulations of repaglinide floating tablets were prepared with different grades of hydroxypropyl methylcellulose (HPMC) and other agents. Evaluation parameters and in vivo bioavailability studies were conducted in the suitable model. Results: Among all the formulations, F21 containing HPMC K1500 PH PRM, Polyox WSR 303, and sodium bicarbonate, as gas generating agent was selected as optimized formulation based on physicochemical properties, floating lag time (36 s), and total floating time (>24 h). From in vitro dissolution studies, the optimized formulation F21 showed drug release of 98.92Â±5.19% within 24 h whereas 95.09Â±5.01% of the drug was released from the marketed product within 1 h. Conclusion: From in vitro and in vivo bioavailability studies repaglinide floating tablets expected to give a new choice for safe, economical, and increased bioavailability for effective management of diabetes mellitus.